(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2026)
The article analyzes the efficiency of irrigation water use in the Mirishkor district from an ecological perspective under climate change conditions. The study examines the district’s natural-geographical features, water resource status, irrigation infrastructure, and ecological impacts (soil salinization, rising groundwater levels, degradation). Ecologically sustainable solutions are also proposed, including the implementation of water-saving technologies, scientifically justified irrigation norms, and the modernization of drainage and monitoring systems. The study results contribute to efficient water use and the maintenance of agroecosystem sustainability in the region.